Thermally conductive composition, thermally conductive sheet using same, and method for producing same
By using a thermally conductive composition composed of a thermosetting resin and thermally conductive particles of different particle sizes, a thermally conductive sheet with high thermal conductivity, compression load and low plasticity is produced, which solves the problem of increasing thermal conductivity with increasing compression load and plasticity in the prior art, and achieves the effect of efficient heat dissipation and low physical load.
Patent Information
- Application Number
- CN202480003686.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-06
- Filing Date
- 2024-02-29
- Publication Date
- 2025-03-28
AI Technical Summary
While the conventional thermal conductivity composition and thermal conductivity sheets increase the compression load and plasticity, it is difficult to take into account both high thermal conductivity and low compression load and plasticity.
A thermally conductive composition consisting of a matrix resin formed of a thermosetting resin, a curing catalyst and thermally conductive particles, wherein the thermally conductive particles contain aluminum nitride and aluminum oxide of different particle sizes, and the thermally conductive sheet is made by vacuum defoaming, calendering and sheet-shaped heating after heating.
The thermal conductivity sheet with high thermal conductivity and low compression load and plasticity suppression is achieved. It is suitable for thermal interface materials between the heating part and the heat dissipation body, improving the heat dissipation efficiency and reducing the physical load on the heating part.
Smart Images

Figure CN119731274A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a thermally conductive composition that is suitably interposed between a heat generating portion of an electric or electronic component and a heat sink, a thermally conductive sheet using the composition, and a method for producing the composition. Background Art
[0002] In recent years, the performance of semiconductors such as CPUs has improved dramatically, but the heat generation has also increased dramatically. Therefore, heat sinks are installed in electrical and electronic components that generate heat, and thermally conductive sheets are used to improve the adhesion between semiconductors and heat dissipation parts. With the miniaturization, high performance, and high integration of equipment, thermally conductive sheets are required to have flexibility and high thermal conductivity. In the past, Japanese Patent No. 6246986 and Japanese Patent No. 7039157 proposed polysiloxane compositions containing large-diameter aluminum nitride particles and small-diameter aluminum nitride particles or aluminum oxide particles. Japanese Patent No. 7082563 and Japanese Patent No. 7205554 proposed thermally conductive polysiloxane compositions containing aluminum nitride particles. Summary of the invention
[0003] The thermally conductive composition of the present invention is a thermally conductive composition comprising a matrix resin (component A) formed of a thermosetting resin, a curing catalyst, and thermally conductive particles (component B), wherein:
[0004] 1500 to 3000 parts by mass of the thermally conductive particles (component B) are added to 100 parts by mass of the matrix resin (component A).
[0005] The thermally conductive particles (component B) contain the following components B-1, B-2, B-3 and B-4,
[0006] The thermally conductive particles (component B) contain, when the total amount of the thermally conductive particles (component B) is 100% by mass:
[0007] Aluminum nitride (component B-1) having a D50 (median particle size) of less than 20 μm: 10 to 20% by mass,
[0008] Aluminum nitride (component B-2) having a D50 (median particle size) of 20 μm or more: 3 to 9 mass %,
[0009] Alumina (component B-3) having a D50 (median particle size) of 60 to 80 μm: 50 to 60% by mass, and
[0010] Alumina having a D50 (median particle size) of less than 60 μm (component B-4): 11 to 37% by mass
[0011] The blending ratio (B-1) / (B-2) of the B-1 component and the B-2 component is 1.2 to 3 in terms of mass ratio. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a schematic cross-sectional view showing a method of using a thermal conductive sheet according to one embodiment of the present invention.
[0013] Figure 2 This is a scanning electron microscope (SEM) photograph of spherical alumina (B-3, D50=75 μm) according to one embodiment of the present invention.
[0014] Figure 3 This is a scanning electron microscope (SEM) photograph of the circular AIN (B-1, D50=5 μm) of the present invention.
[0015] Figure 4 This is a scanning electron microscope (SEM) photograph of the amorphous alumina (B-4, D50=4 μm) of the present invention.
[0016] Figure 5 is a schematic side cross-sectional view of a compressive load detection device used in one embodiment of the present invention.
[0017] Figure 6 AB is a schematic explanatory diagram showing a method for measuring the thermal conductivity of a sample in one example of the present invention. DETAILED DESCRIPTION
[0018] However, conventional thermally conductive compositions and thermally conductive sheets using the same have a problem in that when the thermal conductivity is increased, the compressive load and plasticity increase.
[0019] The present invention aims to solve the above-mentioned conventional problems and provides a thermally conductive sheet having high thermal conductivity and capable of suppressing compressive load and plasticity to be low, a thermally conductive composition as a raw material thereof, and a method for producing a thermally conductive sheet using the same.
[0020] The thermally conductive composition of the present invention is a thermally conductive composition comprising a matrix resin (component A) formed of a thermosetting resin, a curing catalyst, and thermally conductive particles (component B), wherein 1500 to 3000 parts by mass of the thermally conductive particles (component B) are blended with respect to 100 parts by mass of the matrix resin (component A), the thermally conductive particles (component B) contain the following components B-1, B-2, B-3, and B-4, and when the total amount of the thermally conductive particles (component B) is 100% by mass, the thermally conductive particles (component B) contain:
[0021] Aluminum nitride (component B-1) having a D50 (median particle size) of less than 20 μm: 10 to 20% by mass,
[0022] Aluminum nitride (component B-2) having a D50 (median particle size) of 20 μm or more: 3 to 9 mass %,
[0023] Alumina (component B-3) having a D50 (median particle size) of 60 to 80 μm: 50 to 60% by mass, and
[0024] Alumina having a D50 (median particle size) of less than 60 μm (component B-4): 11 to 37% by mass
[0025] The blending ratio (B-1) / (B-2) of the B-1 component and the B-2 component is 1.2 to 3 in terms of mass ratio.
[0026] The thermally conductive sheet of the present invention contains the thermally conductive composition described above and is formed into a sheet shape.
[0027] The method for producing a thermally conductive sheet of the present invention comprises the step of producing a thermally conductive sheet by subjecting the thermally conductive composition to vacuum degassing, rolling, and sheet-forming, followed by heat curing.
[0028] The present invention provides a thermally conductive sheet having high thermal conductivity and capable of suppressing compressive load and plasticity to a low level, and a thermally conductive composition, which is a raw material thereof, and a method for manufacturing the thermally conductive sheet by specifying the above-mentioned composition. Specifically, the plasticity of the thermally conductive composition before curing after degassing is preferably 60 or less, and the instantaneous load value of the cured product of the thermally conductive composition having a diameter of 28.6 mm and a thickness of 2 mm when compressed by 50% is preferably 1000 N or less, and the preferred thermal conductivity is 7 W / m·K or more. In addition, the method for manufacturing the thermally conductive sheet of the present invention can continuously perform sheet forming because the thermally conductive composition of the present invention has low plasticity and good formability.
[0029] The present invention is a thermally conductive composition comprising a matrix resin (component A), a curing catalyst (component C), and thermally conductive particles (component B).
[0030] <Matrix Resin (Component A)>
[0031] The above-mentioned matrix resin is formed by a thermosetting resin. As the above-mentioned thermosetting resin, silicone resin epoxy resin, phenolic resin, unsaturated polyester resin, melamine resin, acrylic resin, silicone resin, fluororesin, etc. can be listed, among which silicone resin is preferred. As a thermosetting resin, forms such as rubber, elastomer, gel, putty or grease can be listed. Specifically, the above-mentioned thermosetting resin can be listed as silicone rubber, silica gel, acrylic rubber, fluororubber, etc. The silicone resin can also be cured by any method such as peroxide, addition, condensation, etc. As the above-mentioned thermosetting resin, silicone resin is preferred because of its high heat resistance. The above-mentioned matrix resin is preferably formed by at least one selected from addition-cured silicone polymers, peroxide-cured silicone polymers and condensed silicone polymers. In addition, based on the reasons such as non-corrosiveness to the surroundings, less by-products discharged outside the system, and being able to be effectively cured to the deep part, the above-mentioned silicone resin is preferably an addition-cured type.
[0032] The above-mentioned base resin preferably further contains a silane coupling agent. Specifically, it is preferred to add 0.1 to 10 parts by mass of the silane coupling agent relative to 100 parts by mass of the above-mentioned base resin, and it is more preferred to add 0.5 to 7 parts by mass. The silane coupling agent covers the surface of the thermally conductive particles (component B) (surface treatment) to make it easier to fill in the base resin (component A) (plasticizer function), and at the same time has the effect of preventing the curing catalyst (component C) from being adsorbed on the thermally conductive particles (component B) and preventing curing from being hindered. If the above-mentioned base resin further contains a silane coupling agent, it has the advantage of excellent storage stability of the thermally conductive composition.
[0033] The above-mentioned silane coupling agent can be exemplified by the formula R(CH3) a Si(OR') 4-a (R is an unsubstituted or substituted organic group having 1 to 20 carbon atoms, R' is an alkyl group having 1 to 4 carbon atoms, and a is 0 or 1) or a partial hydrolyzate thereof. a Si(OR') 4-a(R is an unsubstituted or substituted organic group having 1 to 20 carbon atoms, R' is an alkyl group having 1 to 4 carbon atoms, and a is 0 or 1) represented by a silane compound (hereinafter simply referred to as "silane"), for example, methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, pentyltrimethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane, octadecyltriethoxysilane and the like silane compounds. The above-mentioned silane compounds can be used alone or in combination of two or more.
[0034] The matrix resin preferably contains a base polymer component (component A1) and a crosslinking component (A2).
[0035] (1) Base polymer component (component A1)
[0036] The base polymer component is, for example, an organopolysiloxane containing two alkenyl groups bonded to silicon atoms in one molecule. The above-mentioned organopolysiloxane is the main agent (base polymer component) in the matrix resin of the present invention. The organopolysiloxane has two or more alkenyl groups in one molecule, and the alkenyl groups are vinyl groups, allyl groups, and other alkenyl groups having 2 to 8 carbon atoms, especially 2 to 6 carbon atoms, bonded to silicon atoms. From the perspectives of workability, curability, etc., the viscosity of the above-mentioned organopolysiloxane is preferably 10 to 1,000,000 mPa·s at 25°C, and more preferably 100 to 100,000 mPa·s.
[0037] Specifically, an organopolysiloxane represented by the following general formula (I) can be used, which contains an alkenyl group bonded to a silicon atom at both ends of the molecular chain in one molecule. The organopolysiloxane is a straight-chain organopolysiloxane whose side chains are terminated with an alkyl group. As an organopolysiloxane, from the perspective of workability and curability, it is preferred that the viscosity at 25°C is 10 to 1000000 mPa·s. In addition, the straight-chain organopolysiloxane may also be an organopolysiloxane containing a small amount of branched structure (trifunctional siloxane unit) in the molecular chain.
[0038] [Chemical formula 1]
[0039]
[0040] In the formula,
[0041] Each R 1 are the same as or different from each other and are unsubstituted or substituted monovalent hydrocarbon groups having no aliphatic unsaturated bonds,
[0042] R2 is alkenyl,
[0043] k is 0 or a positive integer.
[0044] In the general formula (I), R 1 The unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond is preferably a hydrocarbon group having 1 to 10 carbon atoms, and particularly preferably a hydrocarbon group having 1 to 6 carbon atoms. Specifically, the unsubstituted monovalent hydrocarbon group having no aliphatic unsaturated bond includes alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, and decyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; and aralkyl groups such as benzyl, phenylethyl, and phenylpropyl. As the substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, examples include halogenated alkyl groups such as chloromethyl, chloropropyl, bromoethyl, and trifluoropropyl, and cyanoethyl, in which a part or all of the hydrogen atoms of the unsubstituted monovalent hydrocarbon group are substituted with halogen atoms such as fluorine, bromine, and chlorine, or cyano.
[0045] In the general formula (I), R 2 The alkenyl group is preferably an alkenyl group having 2 to 6 carbon atoms, and more preferably an alkenyl group having 2 to 3 carbon atoms. Specific examples of the alkenyl group include vinyl, allyl, propenyl, isopropenyl, butenyl, isobutenyl, hexenyl, and cyclohexenyl, and vinyl is preferred.
[0046] In the general formula (I), k is 0 or a positive integer, preferably 0 or a positive integer satisfying 0≤k≤10000, more preferably an integer satisfying 5≤k≤2000, and further preferably an integer satisfying 10≤k≤1200.
[0047] The organopolysiloxane as component A1 may be used in combination with an organopolysiloxane having 3 or more, usually 3 to 30, preferably about 3 to 20, alkenyl groups such as vinyl and allyl groups having 2 to 8 carbon atoms, especially 2 to 6 carbon atoms, bonded to silicon atoms in one molecule. The molecular structure of the organopolysiloxane used in combination may be any of a linear, cyclic, branched, and three-dimensional network structure. The organopolysiloxane used in combination is preferably a linear organopolysiloxane having a main chain composed of a repeating diorganosiloxane unit and having both ends of the molecular chain capped with a triorganosiloxane group and a viscosity of 10 to 1000000 mPa·s, especially 100 to 100000 mPa·s at 25°C.
[0048] In an organopolysiloxane having two or more alkenyl groups bonded to silicon atoms in one molecule, the alkenyl group may be bonded to any part of the molecule. For example, an alkenyl group bonded to a silicon atom at a molecular chain terminal or a non-terminal molecular chain (in the middle of the molecular chain) may also be contained. Among them, the following straight-chain organopolysiloxane represented by the following general formula (chemical formula II) is preferred. From the perspective of workability, curability, etc., the straight-chain organopolysiloxane has 1 to 3 alkenyl groups on the silicon atoms at both ends of the molecular chain, and the viscosity at 25°C is 10 to 1000000 mPa·s. However, in the case where the alkenyl groups bonded to the silicon atoms at the ends of the molecular chain are 1 or 2 in total at both ends, it is preferred to use a straight-chain organopolysiloxane in which the alkenyl groups bonded to the silicon atoms at the non-terminal molecular chain (in the middle of the molecular chain) are used as substituents in the diorganosiloxane unit. Furthermore, the linear organopolysiloxane may be a linear organopolysiloxane containing a small amount of branched structure (trifunctional siloxane unit) in the molecular chain.
[0049] [Chemical formula 2]
[0050]
[0051] In the formula,
[0052] Each R 3 are the same as or different from each other, are unsubstituted or substituted monovalent hydrocarbon groups, at least one of which is an alkenyl group,
[0053] Each R 4 are the same as or different from each other and are unsubstituted or substituted monovalent hydrocarbon groups having no aliphatic unsaturated bonds,
[0054] R 5 is alkenyl,
[0055] l and m are independent of each other and are 0 or positive integers.
[0056] In the general formula (II), R 3 The unsubstituted or substituted monovalent hydrocarbon group is preferably a hydrocarbon group having 1 to 10 carbon atoms, particularly 1 to 6 carbon atoms. Specifically, examples of the unsubstituted monovalent hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, and decyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl, phenylethyl, and phenylpropyl; and alkenyl groups such as vinyl, allyl, propenyl, isopropenyl, butenyl, hexenyl, cyclohexenyl, and octenyl. Examples of the substituted monovalent hydrocarbon group include haloalkyl groups such as chloromethyl, chloropropyl, bromoethyl, and trifluoropropyl, and cyanoethyl groups, in which a part or all of the hydrogen atoms of the unsubstituted monovalent hydrocarbon group are replaced with halogen atoms such as fluorine, bromine, and chlorine, or cyano.
[0057] In the general formula (II), R 4 The unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond is also preferably a hydrocarbon group having 1 to 10 carbon atoms, particularly 1 to 6 carbon atoms. 4 The unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond can be exemplified by the same group as R 1 Specific examples of the unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond are the same groups except that the alkenyl group is not included.
[0058] In the general formula (II), R 5 The alkenyl group is preferably an alkenyl group having 2 to 6 carbon atoms, particularly 2 to 3 carbon atoms, and specifically, R of the above formula (I) can be exemplified. 2 The same group as the alkenyl group of , preferably a vinyl group.
[0059] In the general formula (II), l and m are independent of each other and are 0 or a positive integer, preferably 0 or a positive integer satisfying 0<l+m≤10000, preferably 5≤l+m≤2000, more preferably 10≤l+m≤1200, and preferably 0<l / (l+m)≤0.2, more preferably 0.0011≤l / (l+m)≤0.1.
[0060] (2) Cross-linking component (component A2)
[0061] The crosslinking component of the A2 component of the present invention is, for example, an organohydrogenpolysiloxane. The organohydrogenpolysiloxane acts as a crosslinking agent. The SiH group in the organohydrogenpolysiloxane and the alkenyl group in the organohydrogenpolysiloxane of the A1 component form a cured product through an addition reaction (hydrosilylation). The above-mentioned organohydrogenpolysiloxane can be used as a crosslinking component (component A2) as long as it has two or more hydrogen atoms (i.e., SiH groups) bonded to silicon atoms in one molecule. The molecular structure of the organohydrogenpolysiloxane can also be any one of a linear, cyclic, branched, and three-dimensional network structure. In addition, an organohydrogenpolysiloxane in which the number of silicon atoms in one molecule of the organohydrogenpolysiloxane (i.e., the degree of polymerization) is in the range of 2 to 1000, especially in the range of 2 to 300, can be preferably used as the crosslinking component (component A2).
[0062] The organohydrogenpolysiloxane contains SiH groups as described above. In the organohydrogenpolysiloxane, the position of the SiH group is not particularly limited, and may be at the end of the molecular chain or at a non-end of the molecular chain (in the middle of the molecular chain). In addition, as organic groups other than hydrogen atoms bonded to silicon atoms, the following can be cited: 1 The same applies to unsubstituted or substituted monovalent hydrocarbon groups having no aliphatic unsaturated bonds.
[0063] Examples of the organohydrogenpolysiloxane of the component A2 include those represented by the following formula (III).
[0064] [Chemical formula 3]
[0065]
[0066] In the above formula,
[0067] Each R 6 The same as or different from each other are alkyl groups, phenyl groups, epoxy groups, acryloyl groups, methacryloyl groups, alkoxy groups or hydrogen atoms, and at least two of them are hydrogen atoms.
[0068] L is an integer of 0 to 1000, preferably an integer of 0 to 300,
[0069] M is an integer from 1 to 200.
[0070] <Curing Catalyst (Component C)>
[0071] As the catalyst component of component C, a catalyst used in a hydrosilylation reaction can be used. Examples of the curing catalyst include platinum black, platinum chloride, chloroplatinic acid, a reaction product of chloroplatinic acid and a monohydric alcohol, a complex of chloroplatinic acid and an olefin or vinyl siloxane, a complex of platinum and vinyl disiloxane, a platinum-based catalyst such as diacetylacetate platinum, a palladium-based catalyst, a rhodium-based catalyst and other platinum-based metal catalysts. In addition, a two-component curable silicone polymer generally contains a platinum-based metal catalyst, but in the thermal conductive composition of the present invention, even when a two-component curable silicone polymer is contained, it is preferred to add an additional platinum-based metal catalyst to the thermal conductive composition of the present invention. The addition of the platinum-based metal catalyst is to control the curing rate of the thermal conductive composition.
[0072] The curing catalyst is contained in the thermally conductive composition in an amount of, for example, 0.01 to 1000 parts by mass, preferably 0.1 to 100 parts by mass, and more preferably 0.5 to 50 parts by mass, based on 100 parts by mass of the matrix resin (component A).
[0073] <Thermal Conductive Particles (Component B)>
[0074] The thermally conductive particles (component B) contain the following components B-1, B-2, B-3 and B-4.
[0075] When the total amount of the thermally conductive particles (component B) is 100% by mass, the thermally conductive particles (component B) include:
[0076] Aluminum nitride (component B-1) having a D50 (median particle size) of less than 20 μm: 10 to 20% by mass,
[0077] Aluminum nitride (component B-2) having a D50 (median particle size) of 20 μm or more: 3 to 9 mass %,
[0078] Alumina (component B-3) having a D50 (median particle size) of 60 to 80 μm: 50 to 60% by mass, and
[0079] Alumina having a D50 (median particle size) of less than 60 μm (component B-4): 11 to 37% by mass.
[0080] When the total amount of the thermally conductive particles (component B) is 100% by mass, the thermally conductive particles (component B) preferably contain:
[0081] Aluminum nitride (component B-1) having a D50 (median particle size) of less than 20 μm: 10 to 18% by mass,
[0082] Aluminum nitride (component B-2) having a D50 (median particle size) of 20 μm or more: 3.5 to 8.5 mass %,
[0083] Alumina (component B-3) having a D50 (median particle size) of 60 to 80 μm: 50 to 58% by mass, and
[0084] Alumina having a D50 (median particle size) of less than 60 μm (component B-4): 15 to 35% by mass.
[0085] When the total amount of the thermally conductive particles (component B) is 100% by mass, the thermally conductive particles (component B) more preferably contain:
[0086] Aluminum nitride (component B-1) having a D50 (median particle size) of less than 20 μm: 10 to 16% by mass,
[0087] Aluminum nitride (component B-2) having a D50 (median particle size) of 20 μm or more: 4 to 8% by mass,
[0088] Alumina (component B-3) having a D50 (median particle size) of 60 to 80 μm: 51 to 58% by mass, and
[0089] Alumina having a D50 (median particle size) of less than 60 μm (component B-4): 20 to 33% by mass.
[0090] In the present invention, the thermally conductive particles (component B) are used in combination with a plurality of thermally conductive inorganic particles having different average particle diameters. In this way, thermally conductive inorganic particles having small particle diameters are buried between large particles, and can be filled in a state close to the densest packing, thereby improving the thermal conductivity of the cured thermally conductive composition. In addition, in this way, a cured thermally conductive composition having low plasticity and good forming processability can be obtained. In addition, in this way, the cured thermally conductive composition can be formed into a heat sink: TIM (Thermal Interface Material) having a low compressive load and good handling properties compared to a putty-like cured product.
[0091] The mixing ratio (B-1) / (B-2) of the above-mentioned B-1 component and B-2 component is 1.2 to 3, preferably 1.3 to 2.9, and more preferably 1.3 to 2.8 in terms of mass ratio. This is because, if such a mixing ratio is adopted, a cured product of a thermally conductive composition having high thermal conductivity and low compression load and plasticity can be obtained.
[0092] The thermally conductive particles (component B) are mixed in an amount of 1500 to 3000 parts by mass relative to 100 parts by mass of the matrix resin (component A). The amount of the thermally conductive particles (component B) mixed in an amount of 1700 to 2800 parts by mass relative to 100 parts by mass of the matrix resin (component A) is preferably 2000 to 2500 parts by mass. This is because if such a mixing ratio is adopted, a cured product of a thermally conductive composition having high thermal conductivity and low compression load and plasticity can be obtained.
[0093] The above-mentioned B-1 component, B-2 component and B-4 component are preferably rounded or amorphous crushed particles. In addition, rounded or amorphous crushed particles are easy to obtain and are therefore preferred. In the following, amorphous crushed particles are simply referred to as amorphous. In addition, the above-mentioned B-3 component is preferably spherical. When the B-3 component is spherical, it becomes easy to mix the thermally conductive composition.
[0094] In the thermally conductive particles (component B), the total mass of aluminum oxide / the total mass of aluminum nitride is preferably 4 to 5.5, and more preferably 4.1 to 5.3. This is because increasing the total mass of aluminum oxide can reduce the production cost of the thermally conductive composition. Figure 2 : shows a scanning electron microscope (SEM) photograph of spherical alumina (B-3, D50 = 75 μm) used in the present invention, Figure 3 , a scanning electron microscope (SEM) photograph of a circular AIN (B-1, D50=5 μm) used in the present invention is shown in FIG. Figure 4 : A scanning electron microscope (SEM) photograph of amorphous aluminum oxide (B-4, D50=4 μm) is shown in FIG.
[0095] <Other additives>
[0096] In the thermally conductive composition of the present invention, components other than the above-mentioned components may be added as needed. For example, heat resistance enhancers such as red iron oxide, titanium oxide, cerium oxide, flame retardant aids, curing delay agents, etc. may be added to the thermally conductive composition. In addition, organic or inorganic pigments may be added to the thermally conductive composition for the purpose of coloring or toning. In addition, the above-mentioned silane coupling agent may be added to the thermally conductive composition.
[0097] <Thermal Conductive Composition (Compound)>
[0098] The thermally conductive composition of the present invention can be cured by heating or the like.
[0099] The thermal conductivity of the cured product of the thermally conductive composition is preferably 7 W / m·K or more, more preferably 7 to 15 W / m·K, and even more preferably 7 to 14 W / m·K. The cured product having such a thermal conductivity is suitable as a heat sink: TIM (Thermal Interface Material).
[0100] The instantaneous load value of the cured product of the thermally conductive composition when compressed by 50% with a diameter of 28.6 mm and a thickness of 2 mm is preferably 1000N or less, more preferably 950N or less, and further preferably 900N or less, in the measurement according to ASTM D575-91:2012. As a result, the cured product becomes easy to be flattened, and when it is between the heat generating portion and the heat sink, the physical load on the heat generating portion can be reduced. In addition, the constant load value of the cured product of the thermally conductive composition when compressed by 50% with a diameter of 28.6 mm and a thickness of 2 mm is preferably 1000N or less, more preferably 950N or less, and further preferably 900N or less, in the measurement according to ASTM D575-91:2012. As a result, the cured product becomes easy to be flattened, and when it is between the heat generating portion and the heat sink, the physical load on the heat generating portion can be reduced.
[0101] The plasticity of the thermally conductive composition after degassing before curing is preferably 60 or less, more preferably 10 to 60, further preferably 20 to 55, and particularly preferably 30 to 50. Such a thermally conductive composition with low plasticity has good formability. The above plasticity is obtained as follows: According to JIS K6300-3 and ISO 2007:1991, a sample is compressed between two metal plates with a fixed load (100N) and a fixed time (15 seconds) at a measuring temperature of 25°C using a Wallace plastometer, and the thickness (t) of the compressed sample is divided by the thickness (t0) of the sample before compression, and the obtained value is obtained as plasticity (P0=t / t0×100). The smaller P0 is, the softer it is. Since the thermally conductive composition is formed into a sheet after degassing, the plasticity after degassing before curing is important.
[0102] The thermally conductive composition of the present invention has high versatility when formed into a sheet, and is suitable as a TIM. The thickness of the sheet containing the thermally conductive composition (ie, thermally conductive sheet) is preferably in the range of 0.2 to 10 mm.
[0103] The method for producing a thermally conductive sheet of the present invention comprises the steps of vacuum degassing, calendering, and sheet-forming the thermally conductive composition, and then heating and curing the composition to obtain a thermally conductive sheet. The vacuum degassing is performed by reducing the pressure of the thermally conductive composition to -0.08 to -0.1 Pa, leaving it for about 5 to 10 minutes, and degassing. The calendering may include roll calendering, stamping, etc., but roll calendering is preferred because it can be produced continuously.
[0104] The dielectric breakdown voltage (JIS K6249) of the thermally conductive composition is preferably 7 to 16 kV / mm. Thus, when the thermally conductive composition is cured, a thermally conductive sheet having high electrical insulation can be formed.
[0105] The volume resistivity (JIS K6249) of the thermally conductive composition is preferably 10 10 ~10 14 Thus, when the thermally conductive composition is cured, a thermally conductive sheet having high electrical insulation properties can be formed.
[0106] As an example of the thermally conductive composition of the present invention, an addition reaction type silicone composition (uncured composition) is preferred, and a composite having the following composition is more preferred.
[0107] (Component A) Base resin
[0108] The matrix resin contains the following (A1) and (A2).
[0109] (A1) Base polymer component: a linear organopolysiloxane containing at least two alkenyl groups bonded to silicon atoms in one molecule
[0110] (A2) Crosslinking component: an organohydrogenpolysiloxane containing at least two SH groups in one molecule, in an amount of less than 1 mol per 1 mol of the silicon-bonded alkenyl groups in the above-mentioned component A1
[0111] In addition to the above-mentioned (A1) (A2) components, an organopolysiloxane having no reactive group, for example, unreacted silicone oil such as dimethylpolysiloxane may be contained.
[0112] The total amount of the base polymer component (A1), the crosslinking component (A2), the unreacted silicone oil, and the silane coupling agent was set to 100 parts by mass.
[0113] (Component B) the curing catalyst and (component C) the thermally conductive particles are as described above.
[0114] (C) Platinum metal catalyst: 0.01 to 1000 ppm by mass relative to the base resin (component A)
[0115] (D) Other additives: Contains any amount of silane coupling agent, curing retarder, colorant, etc.
[0116] The following is a description using the accompanying drawings. In the following drawings, the same reference numerals represent the same objects. Figure 1 : is a schematic cross-sectional view of a heat conductive sheet in one embodiment of the present invention assembled in a heat dissipation structure 30. The heat conductive sheet 31b is a component for dissipating heat generated by an electronic component 33 such as a semiconductor element, and is fixed to a main surface 32a of a heat sink 32 that is opposite to the electronic component 33, and is sandwiched between the electronic component 33 and the heat sink 32. In addition, the heat conductive sheet 31a is sandwiched between the heat sink 32 and the heat absorber 35. Moreover, the heat conductive sheets 31a and 31b together with the heat sink 32 form a heat dissipation component that dissipates heat from the electronic component 33. The heat sink 32 is formed in a square plate shape, for example, and has a main surface 32a that is opposite to the electronic component 33, and a side wall 32b that is erected along the outer periphery of the main surface 32a. Heat sink 32 has thermally conductive sheet 31b on main surface 32a surrounded by side wall 32b, and heat absorber 35 is provided on other surface 32c opposite to main surface 32a via thermally conductive sheet 31a. Electronic component 33 is a semiconductor element such as BGA, mounted on wiring board 34.
[0117] The present invention includes the following aspects.
[0118] [Item 1] A thermally conductive composition comprising a matrix resin (component A) formed of a thermosetting resin, a curing catalyst, and thermally conductive particles (component B), wherein:
[0119] 1500 to 3000 parts by mass of the thermally conductive particles (component B) are added to 100 parts by mass of the matrix resin (component A).
[0120] The thermally conductive particles (component B) contain the following components B-1, B-2, B-3 and B-4,
[0121] When the total amount of the thermally conductive particles (component B) is 100 mass %, the thermally conductive particles (component B) include:
[0122] Aluminum nitride (component B-1) having a D50 (median particle size) of less than 20 μm: 10 to 20% by mass,
[0123] Aluminum nitride (component B-2) having a D50 (median particle size) of 20 μm or more: 3 to 9 mass %,
[0124] Alumina (component B-3) having a D50 (median particle size) of 60 to 80 μm: 50 to 60% by mass, and
[0125] Alumina having a D50 (median particle size) of less than 60 μm (component B-4): 11 to 37% by mass
[0126] The blending ratio (B-1) / (B-2) of the B-1 component and the B-2 component is 1.2 to 3 in terms of mass ratio.
[0127] [Item 2] The thermally conductive composition according to Item 1, wherein a cured product of the thermally conductive composition has a thermal conductivity of 7 W / m·K or more, preferably 7 to 15 W / m·K, and more preferably 7 to 15 W / m·K.
[0128] [Item 3] The thermally conductive composition according to Item 1 or 2, wherein the instantaneous load value of the cured product of the thermally conductive composition at 50% compression with a diameter of 28.6 mm and a thickness of 2 mm, measured in accordance with ASTM D575-91:2012, is 1000 N or less, preferably 950 N or less, and more preferably 900 N or less.
[0129] [Item 4] The thermally conductive composition according to any one of Items 1 to 3, wherein the plasticity of the thermally conductive composition after degassing before curing is 60 or less, preferably 10 to 60, more preferably 20 to 55, and even more preferably 30 to 50.
[0130] [Item 5] The thermally conductive composition according to any one of Items 1 to 4, wherein the thermosetting resin is preferably selected from silicone resin, epoxy resin, phenolic resin, unsaturated polyester resin, melamine resin, acrylic resin, silicone resin and fluororesin, and is more preferably silicone resin.
[0131] [Item 6] The thermally conductive composition according to any one of Items 1 to 5, wherein the matrix resin is at least one selected from an addition-curable silicone polymer, a peroxide-curable silicone polymer, and a condensation-type silicone polymer.
[0132] [Item 7] The thermally conductive composition according to any one of Items 1 to 6, wherein the matrix resin preferably further contains a silane coupling agent, and more preferably further contains 0.1 to 10 parts by mass of the silane coupling agent per 100 parts by mass of the matrix resin.
[0133] [Item 8] The thermally conductive composition according to Item 7, wherein the silane coupling agent is a silane having a formula of R(CH3) a Si(OR') 4-a (R is an unsubstituted or substituted organic group having 1 to 20 carbon atoms, R' is an alkyl group having 1 to 4 carbon atoms, and a is 0 or 1) or a partial hydrolyzate thereof, preferably methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, pentyltrimethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane or octadecyltriethoxysilane.
[0134] [Item 9] The thermally conductive composition according to any one of Items 1 to 8, wherein, when the total amount of the thermally conductive particles (component B) is set to 100% by mass, the thermally conductive particles (component B) preferably contain:
[0135] Aluminum nitride (component B-1) having a D50 (median particle size) of less than 20 μm: 10 to 18% by mass,
[0136] Aluminum nitride (component B-2) having a D50 (median particle size) of 20 μm or more: 3.5 to 8.5 mass %,
[0137] Alumina (component B-3) having a D50 (median particle size) of 60 to 80 μm: 50 to 58% by mass, and
[0138] Alumina having a D50 (median particle size) of less than 60 μm (component B-4): 15 to 35% by mass
[0139] When the total amount of the thermally conductive particles (component B) is 100% by mass, the thermally conductive particles (component B) more preferably contain:
[0140] Aluminum nitride (component B-1) having a D50 (median particle size) of less than 20 μm: 10 to 16% by mass,
[0141] Aluminum nitride (component B-2) having a D50 (median particle size) of 20 μm or more: 4 to 8% by mass,
[0142] Alumina (component B-3) having a D50 (median particle size) of 60 to 80 μm: 51 to 58% by mass, and
[0143] Alumina having a D50 (median particle size) of less than 60 μm (component B-4): 20 to 33% by mass.
[0144] [Item 10] The thermally conductive composition according to any one of Items 1 to 9, wherein the blending ratio (B-1) / (B-2) of the component B-1 to the component B-2 is preferably 1.3 to 2.9, more preferably 1.3 to 2.8, in terms of mass ratio.
[0145] [Item 11] The thermally conductive composition according to any one of Items 1 to 10, wherein the amount of the thermally conductive particles (component B) is preferably 1700 to 2800 parts by mass, and more preferably 2000 to 2500 parts by mass, relative to 100 parts by mass of the matrix resin (component A).
[0146] [Item 12] The thermally conductive composition according to any one of Items 1 to 11, wherein the component B-1, component B-2, and component B-4 are rounded or amorphous crushed particles, and the component B-3 is spherical.
[0147] [Item 13] The thermally conductive composition according to any one of Items 1 to 12, wherein in the thermally conductive particles (component B), the total mass of aluminum oxide / the total mass of aluminum nitride is preferably 4 to 5.5, and more preferably 4.1 to 5.3.
[0148] [Item 14] The thermally conductive composition according to any one of Items 1 to 13, wherein the matrix resin contains a base polymer component (component A1) and a crosslinking component (A2).
[0149] [Item 15] A thermally conductive composition according to any one of Items 1 to 14, wherein the base polymer component is an organopolysiloxane having two or more alkenyl groups bonded to silicon atoms in one molecule, preferably an organopolysiloxane having two or more alkenyl groups having 2 to 8 carbon atoms, especially 2 to 6 carbon atoms, such as vinyl groups or allyl groups, bonded to silicon atoms in one molecule as alkenyl groups, more preferably an organopolysiloxane represented by the general formula (I) containing alkenyl groups bonded to silicon atoms at both ends of the molecular chain in one molecule, or a straight-chain organopolysiloxane represented by the general formula (II) having 1 to 3 alkenyl groups on silicon atoms at both ends of the molecular chain.
[0150] [Chemical formula 4]
[0151]
[0152] In the formula,
[0153] Each R 1 are the same as or different from each other and are unsubstituted or substituted monovalent hydrocarbon groups having no aliphatic unsaturated bonds,
[0154] R 2 is alkenyl,
[0155] K is 0 or a positive integer.
[0156] [Chemical formula 5]
[0157]
[0158] In the formula,
[0159] Each R 3 are the same as or different from each other, are unsubstituted or substituted monovalent hydrocarbon groups, at least one of which is an alkenyl group,
[0160] Each R 4 are the same as or different from each other and are unsubstituted or substituted monovalent hydrocarbon groups having no aliphatic unsaturated bonds,
[0161] R 5 is alkenyl,
[0162] L and m are independent of each other and are 0 or positive integers.
[0163] [Item 16] A thermally conductive composition according to any one of Items 1 to 15, wherein the crosslinking component is an organohydrogenpolysiloxane, preferably an organohydrogenpolysiloxane having two or more hydrogen atoms bonded to silicon atoms (i.e., SiH groups) in one molecule, and more preferably an organohydrogenpolysiloxane represented by the general formula (III).
[0164] [Chemical formula 6]
[0165]
[0166] In the above formula,
[0167] Each R 6 The same as or different from each other are alkyl groups, phenyl groups, epoxy groups, acryloyl groups, methacryloyl groups, alkoxy groups or hydrogen atoms, and at least two of them are hydrogen atoms.
[0168] L is an integer of 0 to 1000, preferably an integer of 0 to 300,
[0169] M is an integer from 1 to 200.
[0170] [Item 17] A thermally conductive composition according to any one of Items 1 to 16, wherein the curing catalyst is a catalyst used in a hydrosilylation reaction, preferably a platinum group metal catalyst such as platinum black, platinum chloride, chloroplatinic acid, a reaction product of chloroplatinic acid and a monohydric alcohol, a complex of chloroplatinic acid and an olefin or vinyl siloxane, a complex of platinum and vinyl disiloxane, diacetylacetate platinum, etc., a palladium-based catalyst, a rhodium-based catalyst, etc.
[0171] [Item 18] The thermally conductive composition is preferably an addition reaction type silicone composition (uncured composition), and more preferably a composite of the following composition.
[0172] (Component A) Base resin
[0173] The matrix resin contains the following (A1) and (A2).
[0174] (A1) Base polymer component: a linear organopolysiloxane containing at least two alkenyl groups bonded to silicon atoms in one molecule
[0175] (A2) crosslinking component: an organohydrogenpolysiloxane containing at least two SH groups in one molecule, in an amount of less than 1 mol per 1 mol of the silicon-bonded alkenyl groups in the A1 component.
[0176] In addition to the above-mentioned components (A1) and (A2), an organopolysiloxane having no reactive group, for example, unreacted silicone oil such as dimethylpolysiloxane may be contained.
[0177] The total amount of the base polymer component (A1), the crosslinking component (A2), the unreacted silicone oil, and the silane coupling agent was set to 100 parts by mass.
[0178] (Component B) the curing catalyst and (component C) the thermally conductive particles are as described in item 1.
[0179] (C) Platinum metal catalyst: 0.01 to 1000 ppm by mass relative to the base resin (component A)
[0180] (D) Other additives: Contains any amount of silane coupling agent, curing retarder, colorant, etc.
[0181] [Item 19] A thermally conductive sheet comprising the thermally conductive composition according to any one of Items 1 to 18 and formed into a sheet.
[0182] [Item 20] The thermally conductive sheet according to Item 19, wherein the thickness of the thermally conductive sheet is in the range of 0.2 to 10 mm.
[0183] [Item 21] A method for producing a thermally conductive sheet, comprising the step of producing the thermally conductive sheet by vacuum degassing, rolling, and sheet-forming the thermally conductive composition according to any one of Items 1 to 18, followed by heat curing.
[0184] [Item 22] The method for producing a thermally conductive sheet according to Item 21, wherein the vacuum degassing is performed by reducing the pressure of the thermally conductive composition to a pressure of -0.08 to -0.1 Pa and leaving the composition to stand for about 5 to 10 minutes for degassing.
[0185] [Example]
[0186] The following examples are used for explanation. The present invention is not limited to the examples. Various parameters were measured by the methods described below.
[0187] <50% Compression Load Value>
[0188] The compression load test method is in accordance with ASTM D575-91:2012. Figure 5 1 is a schematic side cross-sectional view of a compression load detection device used in one embodiment of the present invention. The compression load detection device 1 includes a sample stand 2 and a load cell 6, and a thermal conductive sheet sample 4 is clamped between aluminum plates 3 and 5. Figure 5 The load cell 6 is used to compress the load cell to a predetermined thickness. The maximum load value (“50% compression load value (instant)”) when the thickness is compressed by 50% and the load value (“50% compression load value (constant)”) after the compression is maintained for 1 minute are recorded.
[0189] Measurement conditions
[0190] Specimen: cylindrical (diameter 28.6mm, thickness 2mm)
[0191] Compression: 50%
[0192] Aluminum plate size: round (diameter 28.6mm) (compressed surface)
[0193] Compression speed: 5mm / min
[0194] Compression method: TRIGGER method (a method that uses the point where a 2N load is sensed as the measurement start position)
[0195] Measuring device: MODEL-1310NW manufactured by AIKOH Engineering (load sensor 200kgf)
[0196] <Thermal conductivity>
[0197] The thermal conductivity of the thermally conductive sheet was measured by a transient plane heat source method (Hot Disk, in accordance with ISO22007-2:2008). Figure 6 As shown in Figure A, a polyimide film sensor 12 is sandwiched between two thermally conductive sheet samples 13a and 13b, and constant power is applied to the sensor 12 to make it generate heat. The thermal characteristics are analyzed from the temperature rise value of the sensor 12. The diameter of the top 14 of the sensor 12 is 7 mm. Figure 6 As shown in FIG. 1B, a double helix structure of electrodes is formed, and a current application electrode 15 and a resistance value electrode (temperature measurement electrode) 16 are arranged at the bottom. The thermal conductivity is calculated by the following formula (Formula 1).
[0198] [Mathematical formula 1]
[0199]
[0200] λ: Thermal conductivity (W / m·K)
[0201] P0: Constant power (W)
[0202] r: Radius of the sensor (m)
[0203]
[0204] α: Thermal diffusivity of the sample (m 2 / s)
[0205] t: measurement time (s)
[0206] D(τ): dimensionless function of τ
[0207] ΔT(τ): Temperature rise of the sensor (K)
[0208] <Plasticity>
[0209] Plasticity is determined as follows: According to JIS K 6300-3 and ISO 2007:1991, a Wallace plastometer is used to compress the thermally conductive composition between two metal plates at a measuring temperature of 23°C with a constant load (100N) and a constant time (15 seconds), and the thickness (t) of the thermally conductive composition after compression is divided by the thickness (t0) of the thermally conductive composition before compression, and the obtained value is determined as plasticity (P0=t / t0×100). The larger the P0, the softer it is. The plasticity after degassing before curing is the plasticity of the thermally conductive composition (composite) after degassing for 5 minutes under a reduced pressure of -0.1 Pa.
[0210] (Examples 1 to 6, Comparative Examples 1 to 7)
[0211] 1.Material composition
[0212] (1) Matrix resin (component A)
[0213] A commercially available two-liquid room temperature addition curing silicone polymer (silicone component) containing polyorganosiloxane is used. One liquid (liquid A) contains a base polymer component (polyorganosiloxane, component A1 in component A) and a platinum group metal catalyst, and the other liquid (liquid B) contains a base polymer component (polyorganosiloxane, component A1 in component A) and a crosslinking agent component (component A2 in component A), namely, organohydrogenpolysiloxane. The ratio of liquid A to liquid B is A:B=100:100 by mass. The two-liquid room temperature addition curing silicone polymer is addition cured by mixing at room temperature to become a silicone resin.
[0214] (2) Thermally conductive particles (components B-1 to B-4)
[0215] The thermally conductive particles described in Table 1 were used. The average particle size is D50 (median particle size) of the cumulative particle size distribution based on volume in the particle size distribution measurement based on the laser diffraction light scattering method. As such a measuring instrument, for example, there is a laser diffraction / scattering particle distribution measuring device LA-950S2 manufactured by Horiba, Ltd. In addition, AlN in the table is an abbreviation for aluminum nitride.
[0216] B-1: with round aluminum nitride (D50 = 5 μm)
[0217] B-1: Amorphous aluminum nitride (D50 = 15 μm)
[0218] B-2: with round aluminum nitride (D50 = 20 μm)
[0219] B-2: with round aluminum nitride (D50 = 30 μm)
[0220] B-2: with round aluminum nitride (D50 = 70 μm)
[0221] B-2: with round aluminum nitride (D50 = 100 μm)
[0222] B-3: Spherical alumina (D50 = 75 μm)
[0223] B-4: Amorphous aluminum oxide (D50 = 0.3 μm)
[0224] B-4: Amorphous aluminum oxide (D50 = 0.7 μm)
[0225] B-4: Amorphous aluminum oxide (D50 = 4.0 μm)
[0226] B-4: Amorphous aluminum oxide (D50 = 2.2 μm)
[0227] (3) Curing catalyst (component C)
[0228] As a curing catalyst (component C), a platinum-vinyl disiloxane complex (platinum group metal catalyst) was used. In addition, as described above, the two-liquid curable silicone polymer (silicone component) contains a platinum group metal catalyst. When preparing the thermal conductive composition of each example, an additional platinum group metal catalyst was added to the thermal conductive composition in order to fully cure the polyorganosiloxane.
[0229] (4) Silane coupling agent
[0230] As the silane coupling agent, decyltrimethoxysilane was used.
[0231] 2. Thermally conductive composition (composite)
[0232] The amounts of the materials shown in Table 1 were measured and put into a mixing device to prepare a thermally conductive composition. The thermally conductive composition was degassed at a reduced pressure of -0.1 Pa for 5 minutes.
[0233] 3. Sheet forming processing
[0234] The thermally conductive composition was sandwiched between polyethylene terephthalate (PET) films subjected to mold release treatment, and the thermally conductive composition was roll-formed into a sheet with a thickness of 2.0 mm by constant speed rollers, and then heat-cured at 100° C. for 15 minutes in this state to obtain a thermally conductive sheet (thermal conductive silicone rubber sheet). When the molding processability can be molded under the above conditions, it is judged as "possible", and when it cannot be molded, it is judged as "NG".
[0235] The conditions and results of the examples are shown in Table 1, and the conditions and results of the comparative examples are shown in Table 2. In Tables 1 and 2, the amount of each material is described in terms of the amount (parts by mass) when the base resin (component A, two-liquid room temperature curing type silicone polymer) is set to 100 parts by mass (100 g).
[0236] The specific gravity of the base resin (component A), silane coupling agent, and platinum group metal catalyst is 0.98, the specific gravity of alumina (components B-3 and B-4) is 3.98, and the specific gravity of aluminum nitride (components B-1 and B-2) is 3.32.
[0237] Table 1
[0238] Table 2
[0239]
[0240] *1: Cannot be compounded and cannot be measured.
[0241] From Tables 1 and 2, the following can be seen.
[0242] (1) In Examples 1 to 5, the thermal conductivity of the thermal conductive sheet was high, and the compressive load and the plasticity after degassing before curing were low, compared with Comparative Examples 1 to 6.
[0243] (2) Compared with Comparative Example 1 (component B-1 only), Examples 1 and 2 reduce the load value of the thermal conductive sheet by combining two types of aluminum nitrides (component B-1 and component B-2) having different particle sizes.
[0244] (3) In Examples 1, 3, 4, and 5, even when the component (B-2) having a large particle size was changed in various ways, there was no influence on the load value of the thermal conductive sheet.
[0245] (4) When neither the component (B-1) nor the component (B-2) is contained, or two components (B-2) are contained as in Comparative Examples 1, 3, and 4, the load value of the thermal conductive sheet is high or the thermal conductive composition cannot be mixed therewith.
[0246] (5) The thermal conductivity and load value of the thermal conductive sheets of Comparative Example 5 (the content of the component (B-3) is below the prescribed range) and Comparative Example 6 (the content of the component (B-1) is below the prescribed range) are both low.
[0247] The thermally conductive composition and the thermally conductive sheet of the present invention are suitable as a heat sink: TIM (Thermal Interface Material) interposed between a heat generating portion of an electric or electronic component and a heat sink.
[0248] Explanation of symbols
[0249] 1-Compression load detection device
[0250] 2-Sample table
[0251] 3.5-Aluminum plate
[0252] 4- Thermally conductive sheet sample
[0253] 6-Force sensor
[0254] 11- Thermal conductivity measuring device
[0255] 12 - Sensor
[0256] 13a, 13b - Thermally conductive sheet samples
[0257] 14 - Top of sensor
[0258] 15- Electrode for impressed current
[0259] 16 - Resistance value electrode (temperature measurement electrode)
[0260] 30-Heat dissipation structure
[0261] 31a, 31b - Thermally conductive sheet
[0262] 32 - Radiator
[0263] 32b - Radiator side wall
[0264] 33 - Electronic components
[0265] 34-Wiring substrate
[0266] 35 - Heat sink
Claims
1. A thermally conductive composition comprising a matrix resin (component A) formed of a thermosetting resin, a curing catalyst and thermally conductive particles (component B), wherein: 1500 to 3000 parts by mass of the thermally conductive particles (component B) are added to 100 parts by mass of the matrix resin (component A). The thermally conductive particles (component B) contain the following components B-1, B-2, B-3 and B-4, When the total amount of the thermally conductive particles (component B) is 100 mass %, the thermally conductive particles (component B) include: Aluminum nitride (component B-1) having a D50 (median particle size) of less than 20 μm: 10 to 20% by mass, Aluminum nitride (component B-2) having a D50 (median particle size) of 20 μm or more: 3 to 9 mass %, Alumina (component B-3) having a D50 (median particle size) of 60 to 80 μm: 50 to 60% by mass, and Alumina having a D50 (median particle size) of less than 60 μm (component B-4): 11 to 37% by mass The blending ratio (B-1) / (B-2) of the B-1 component and the B-2 component is 1.2 to 3 in terms of mass ratio.
2. The thermally conductive composition according to claim 1, wherein The thermal conductivity of the cured product of the thermally conductive composition is 7 W / m·K or more.
3. The thermally conductive composition according to claim 1 or 2, wherein The cured product of the thermally conductive composition has an instantaneous load value of 1000 N or less when subjected to 50% compression at a diameter of 28.6 mm and a thickness of 2 mm in a measurement in accordance with ASTM D575-91:2012.
4. The thermally conductive composition according to any one of claims 1 to 3, wherein The thermally conductive composition has a plasticity of 60 or less after degassing before curing.
5. The thermally conductive composition according to any one of claims 1 to 4, wherein The matrix resin is at least one selected from addition-cured silicone polymers, peroxide-cured silicone polymers and condensed silicone polymers.
6. The thermally conductive composition according to any one of claims 1 to 5, wherein 0.1 to 10 parts by mass of a silane coupling agent is further blended with respect to 100 parts by mass of the matrix resin.
7. The thermally conductive composition according to any one of claims 1 to 6, wherein The B-1 component, the B-2 component and the B-4 component are in the form of rounded or amorphous crushed particles, and the B-3 component is in the form of spheres.
8. A thermally conductive sheet, wherein: The thermally conductive composition according to any one of claims 1 to 7 is formed into a sheet shape.
9. The thermally conductive sheet according to claim 8, wherein The thickness of the thermally conductive sheet is in the range of 0.2 to 10 mm.
10. A method for producing a thermally conductive sheet, wherein: The method comprises the step of vacuum degassing, rolling, and sheet-forming the thermally conductive composition according to any one of claims 1 to 7, and then heating and curing the composition to produce a thermally conductive sheet.
Citation Information
Patent Citations
Aluminum nitride substrate and manufacture
JP1987046986A